2019
DOI: 10.1186/s12933-019-0906-1
|View full text |Cite
|
Sign up to set email alerts
|

A functional variant of the dimethylarginine dimethylaminohydrolase-2 gene is associated with myocardial infarction in type 2 diabetic patients

Abstract: Background: Myocardial infarction is the main mortality cause in patients with type 2 diabetes (T2DM). Endothelial dysfunction due to reduced bioavailability of nitric oxide (NO) is an early step of atherogenesis. Asymmetric dimethylarginine (ADMA) is an endogenous inhibitor of NO synthesis, and it is metabolized by the enzymes dimethylarginine dimethylaminohydrolase (DDAH) 1 and 2. The functional variant rs9267551 C, in the promoter region of DDAH2, has been linked to increased DDAH2 expression, and lower ADM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Despite large-scale GWASs providing robust evidence for genetic variants influencing metabolic pathways and CVDs, [19][20][21][22][23][24] it is unclear whether genetic variants exist for CVD within the basis of individual chronic metabolic diseases. The aim of our study was to identify genetic variations associated with CVD among individuals with HTN, DM, and DL, respectively; for which we found varied meaningful loci for CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Despite large-scale GWASs providing robust evidence for genetic variants influencing metabolic pathways and CVDs, [19][20][21][22][23][24] it is unclear whether genetic variants exist for CVD within the basis of individual chronic metabolic diseases. The aim of our study was to identify genetic variations associated with CVD among individuals with HTN, DM, and DL, respectively; for which we found varied meaningful loci for CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic IR was found to be an independent risk factor for GSD ( Biddinger et al, 2008 ; Chang et al, 2008 ); therefore, we infer that ADMA plays a promoting role in the process of gallstone development. ADMA is an endogenous inhibitor of nitric oxide (NO) synthetase, and endothelial dysfunction due to reduced bioavailability of nitric oxide (NO) is a risk factor for atherogenesis ( Qin et al, 2021 ), myocardial infarction ( Mannino et al, 2019 ), and chronic kidney disease ( Shah et al, 2021 ). At the same time, studies have shown that GB hypomotility plays a key role in gallbladder (GB) normal relaxation ( Chen et al, 1997 ; Swartz-Basile et al, 2000 ), while GB hypomotility is also a required factor for gallstone pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite large-scale GWASs providing robust evidence for genetic variants in uencing metabolic pathways and CVDs, [18][19][20][21][22][23] it is unclear whether genetic variants exist for CVD within the basis of individual chronic metabolic diseases. The aim of our study was to identify genetic variations associated with CVD among individuals with HTN, DM, and DL, respectively; for which we found varied meaningful loci for CVD.…”
Section: Discussionmentioning
confidence: 99%